RSV Monoclonal Antibody Implementation for At‐Risk Infants: Victoria, Australia's 2024 Experience - Jane Tuckerman; Daryl R. Cheng; Guillian Hunter; Sonja Elia; Tara Hearn; Deepali Verma; Susan Jacobs; Jeremy Carr; Nigel W. Crawford (Health Science Reports, 2026)
ABSTRACT Background New respiratory syncytial virus (RSV) preventative programs are launching globally. Our Australian jurisdiction implemented RSV monoclonal antibody provision via pediatric and perinatal hospitals for highest risk neonates and infants. The aim of this study was to monitor the implementation and utilization of nirsevimab and palivizumab in a cohort of infants at increased risk who were program recipients in Victorian hospitals in 2024 and provide evidence and operational context for future programs. Methods In this observational cohort study, suitable participants at each site were identified by checking the drug administration records for receipt of nirsevimab and/or palivizumab. Follow‐up of all infants was via the hospital electronic medical record (EMR), with relevant administration information as well as any subsequent respiratory encounters (defined by testing for respiratory pathogens) at either Monash Children's Hospital or the Royal Children's Hospital, Melbourne. This study was descriptive and exploratory, and no formal effectiveness or comparative analyses were undertaken. Results In total, 430 infants received RSV preventatives at five hospital sites throughout Victoria. In total, 54% of infants who received RSV preventatives were premature (< 37 weeks gestation); 45% were < 32 weeks gestation and four infants (2 pre‐term; 2 term) experienced breakthrough infection. Conclusion Without a national program combining maternal and infant preventatives, hospital‐level targeted programs can protect infants at highest risk of severe RSV and reduce admissions; we recommend biopharmaceutical support for these targeted initiatives over large population‐wide programs that have not met cost‐effectiveness criteria—this 2024 approach informed Australia's 2025 RSV program. Findings will inform ongoing RSV special‐risk initiatives.